UTILIZATION OF PLASTIC WASTE INTO ECONOMICALLY VALUABLE HANDICRAFTS - T.Edyansyah; Rico Nur Ilham; Amru Usman; Khairil Anwar; Em Yusuf Iis (RADJA PUBLIKA, 2025)
This training activity on utilizing plastic waste into economically valuable handicraft products is a science and technology application program that can provide solutions to the main problems faced by Partners. Waste that is managed properly will improve the quality of the environment and public health. Recycling plastic waste itself helps the government in managing waste, especially if the management is carried out professionally and commercially, so that it becomes a profitable business. The use of plastic in various types of products is unstoppable. This certainly has an impact on polluting the environment because plastic waste will take a very long time to naturally replenish. In order to reduce plastic waste, we took the initiative to process plastic bottle waste into functional and aesthetic lamp tables. Experimental methods are applied to training programs and trials to make various derivative products made from plastic waste. The solutions offered to the problems faced include providing training in managing used plastic bottle waste into imitation flowers, and providing motivation to Partners that their products will be marketed by considering aspects such as shape, size, function, and color. The results of the program are recognized that plastic waste combined with pipes, sponges, and boxes, by paying attention to design aspects, becomes a selling point for various functional products. The product is expected to be sold so that it can increase the productivity and financial independence of Partners and can reduce the burden of TPA in accommodating plastic waste. The real and practical sustainability of our activities is expected to strengthen the ties between the world of educational institutions and the community.